Anxiety among children a year after the onset of the COVID-19 pandemic: a Brazilian cross-sectional online survey - Garcia de Avila, Marla Andréia; de Jesus Amorin, Tainara; Hamamoto Filho, Pedro Tadao; de Almeida, Graziela Maria Ferraz; Olaya-Contreras, Patricia; Berghammer, Malin; Jenholt Nolbris, Margaretha; Nilsson, Stefan (Frontiers in Public Health, 2024)
Aim This study seeks to build upon a prior investigation into the impact of the COVID-19 pandemic and to evaluate the prevalence of anxiety among Brazilian children, along with its associated factors, one year after the commencement of the pandemic. Design A cross-sectional study. Methods A survey was conducted from April–May 2021 in Brazil. Children aged 6–12 and their guardians from five Brazilian regions were included. The Children’s Anxiety Questionnaire (CAQ; scores 4–12) and Numerical Rating Scale (NRS; scores 0–10) were used to measure anxiety. Results Of the 906 children, 53.3% were girls (average age = 8.79 ± 2.05 years). Mothers responded for 87.1% of the children, and 70.9% were from the Southeast region. Based on a CAQ score of ≥9 and an NRS score of ≥8, the anxiety prevalence was 24.9 and 34.9%, respectively. Using logistic regression, a CAQ ≥9 score was associated with older children and children with chronic disease or disability. An NRS score of ≥8 was associated with reduced family income during the pandemic, the person caring for the children, and with children with chronic disease or disability. Conclusion These findings suggest the need to implement public health actions aimed at children with chronic diseases and disabilities and their parents to guide them regarding the warning signs and negative emotions. This study contributes to characterizing the evolution of the pandemic in Brazil and provides a basis for comparison with the literature from other countries.